Glutamine ameliorates hyperoxia-induced hippocampal damage by attenuating inflammation and apoptosis via the MKP-1/MAPK signaling pathway in neonatal rats - Xuan, Chouhui; Cui, Haixia; Jin, Zhengyong; Yue, Yuyang; Cao, Shuxia; Cui, Songbiao; Xu, Dongyuan (Frontiers in Pharmacology, 2023)
Glutamine (Gln) is an immunomodulatory protein that mediates oxidative stress, inflammation, and apoptosis, but has not been reported in the treatment of hyperoxia (Hyp)-induced brain injury. The aim of this study was to determine whether Gln could improve hyp-induced brain injury in neonatal rats to and later learning and memory dysfunction, and to explore its possible mechanisms. We prepared a model of neonatal rat brain injury caused by normobaric hyperoxia while administered with Gln for 7 days for evaluation. Learning memory function was assessed with the Morris water maze test. Histological analysis, protein expression analysis, oxidative stress and inflammation level analysis were performed using hippocampal tissue. Gln treatment significantly reduced brain tissue water content, oxidative stress levels, microglia activation and inflammatory factor expression, and attenuated tissue damage and apoptosis in the hippocampal region. Gln ameliorates hyp-induced learning, memory impairment in neonatal rats in water maze test. It also increased MKP-1 protein expression and decreased p-p38, p-ERK and p-JNK. Therefore, it is hypothesized that Gln may exert neuroprotective effects by increasing MKP-1 expression to negatively regulate MAPK signaling, with potential cognitive improvement in hyp-induced brain injury.